Asal Usul Dan Status Keperdataan Anak Akibat Pernikahan Siri (Putusan Nomor 241/PDT.P/2022/PA.STB) - Nurmala; Azhar (Peduli Riset dan Pengabdian Masyarakat, 2023)
Children are said to be a legitimate child if he or she is born in a valid marriage and is carried out in accordance with religion and belief and has been registered with a marriage certificate official. In this research, this is a case regarding the application for the origin of a child born from a serial marriage where the parents then remarried in a formal manner. Office of Religious Affairs (KUA). The application for the origin of the child aims to obtain the child's identity in the form of a birth certificate. This case was determined by the Stabat Religious Court with case number 241/Pdt.P/2022/PA.Stb. There are three points that are the main focus of this issue, with the aim of knowing the status of children resulting from unregistered marriages according to the provisions of Islamic law, then the decision of the Stabat Religious Court on the origin of children resulting from unregistered marriages as well as the considerations of the Stabat Religious Court Judges in determining the child's origin case. This study uses a qualitative method. Data analysis using descriptive methods. This type of research uses research methods through normative methods with a case approach obtained from secondary legal materials (literature review). Data collection techniques with documentation supported by interviews as validation. The conclusion of this research is that the petition for the origin of the child was granted by the Panel of Judges at the Stabat Religious Court, determining that a child who is 4 years old is a legitimate child, namely a child born in or resulting from a valid marriage and charging all court costs to the Petitioner.